2012
DOI: 10.1210/jc.2011-3132
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofKCNJ5Mutations on Gene Expression in Aldosterone-Producing Adenomas and Adrenocortical Cells

Abstract: KCNJ5 mutations are prevalent in APA, and our data suggest that these mutations increase expression of CYP11B2 and NR4A2, thus increasing aldosterone production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 18 publications
7
98
3
1
Order By: Relevance
“…Such approaches may illuminate drivers in ∼65% of APCCs that did not harbor candidate drivers by our panel-based approach. Of interest, no well-supported somatic KCNJ5 mutations were observed in our APCCs subjected to NGS, although mutations in KCNJ5 occur in at least 30% of APAs (7,8,17,21). Given that APCCs in our cohort harbored somatic mutations in CACNA1D (26%) and ATP1A1 (9%), at residues previously reported in APA, APCCs may represent a precursor population of cells that lead to APA with these mutations through unknown mechanisms.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Such approaches may illuminate drivers in ∼65% of APCCs that did not harbor candidate drivers by our panel-based approach. Of interest, no well-supported somatic KCNJ5 mutations were observed in our APCCs subjected to NGS, although mutations in KCNJ5 occur in at least 30% of APAs (7,8,17,21). Given that APCCs in our cohort harbored somatic mutations in CACNA1D (26%) and ATP1A1 (9%), at residues previously reported in APA, APCCs may represent a precursor population of cells that lead to APA with these mutations through unknown mechanisms.…”
Section: Discussionmentioning
confidence: 67%
“…However, both of these ZG/ZF-like cells strongly express CYP11B2, consistent with autonomous aldosterone production in APCCs. Recurrent mutations observed in APA are known to cause aldosterone overproduction in in vitro experiments (8,12); therefore, the existence of these mutations in APCCs supports autonomous aldosterone production. Of note, we identified distinct somatic mutations in individual APCCs from the same adrenal gland, which is in contrast to previously studied APAs that have been reported to harbor a single mutation driving aldosterone production.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Monticone et al recently reported a study of steroidogenic enzyme mRNA levels in 47 APAs including 5 Japanese patients, and found all 5 cases to have a mutation of the KCNJ5 gene [19]. Although the details for these 5 cases were not reported, Japanese patients with typical APA may have a high prevalence of somatic mutations of the KCNJ5 gene.…”
Section: Expression Of Steroidogenic Enzymes and Kcnj5 Mrna In Patienmentioning
confidence: 99%
“…10,13,14,[18][19][20][21][22] First, somatic KCNJ5 mutations were more common in female than male patients. Second, in the presence of KCNJ5 mutations, larger tumor size, higher urinary aldosterone, higher aldosterone-renin ratio, and lateralization index were observed, which suggested that excess aldosterone was related to the mutated APA.…”
mentioning
confidence: 99%